Automated tuning of an eight‐channel cardiac transceive array at 7 tesla using piezoelectric actuators. Issue 6 (1st July 2014) - Keith, Graeme A.; Rodgers, Christopher T.; Hess, Aaron T.; Snyder, Carl J.; Vaughan, J. Thomas; Robson, Matthew D.
<x xml:space="preserve">Abstract</x> Purpose Ultra‐high field (UHF) MR scanning in the body requires novel coil designs due to B1 field inhomogeneities. In the transverse electromagnetic field (TEM) design, maximum B1 transmit power can only be achieved if each individual transmit element is tuned and matched for different coil loads, which requires a considerable amount of valuable scanner time. Methods An integrated system for autotuning a multichannel parallel transmit (pTx) cardiac TEM array was devised, using piezoelectric actuators, power monitoring equipment and control software. The reproducibility and performance of the system were tested and the power responses of the coil elements were profiled. An automated optimization method was devised and evaluated. Results The time required to tune an eight‐element pTx cardiac RF array was reduced from a mean of 30 min to less than 10 min with the use of this system. Conclusion Piezoelectric actuators are an attractive means of tuning RF coil arrays to yield more efficient B1 transmission into the subject. An automated mechanism for tuning these elements provides a practical solution for cardiac imaging at UHF, bringing this technology closer to clinical use. Magn Reson Med 73:2390–2397, 2015. © 2014 The Authors. Magnetic Resonance in Medicine published by Wiley Periodicals, Inc. on behalf of International Society for Magnetic Resonance in Medicine.